Análisis biométrico de las características faciales de la población colombiana. Parte I: características cefalométricas - Bojanini, Ana Cristina; Betancur-P., John Jairo; Jones-G., Monica (Revista Facultad de Odontología Universidad de Antioquia, 2016)
At present there are no cephalometric studies statistically valid, that show the applicability of the international cephalometric standards in our population. The purpose of this study was to establish the standards of the prevalent facial morphology in Medellin-Colombia, according to sex and socioeconomical status, and to determine their difference with the foreign standards. Lateral cephalometric radiographs were taken of 106 adults (53 women/53 men), 18 to 29 years of age, with Colombian parents and grandparents; Class I occlusion without evident crowding; good facial harmony; without medical records of orofacial secuelae; without previous orthodontics or facial orthopedics; without congenital abscence of laterals or loss of two contiguous teeth. Twenty-eight cephalometric measurements were analyzed and neither one of them showed difference according to the socioeconomical status. Sexual dimorphism was statistically significant in nine longitudinal measurements, showing that sexual differences are basically in size and not in position. The international standards can be accepted for sixteen of the measurements and only one measurement, Silla-Nasion for men, was statistically smaller than the international standard. The other eleven variables must be used with caution.